Pengaruh Psychological Well-Being Terhadap Kinerja Karyawan: Systematic Literature Review - Wisnu Prasojo; Amelia Putri; Rahma Anita Sari; Dani Rizana (Jurnal Manajemen Kewirausahaan dan Teknologi, 2025)
This study aims to provide a comprehensive understanding of how psychological well-being (PWB) influences employee performance through a Systematic Literature Review approach. By analyzing a range of relevant and open-access studies, this review synthesizes key findings to identify patterns that explain the relationship between psychological well-being and work outcomes. The analysis reveals that PWB is a crucial internal factor shaping productive, stable, and consistent employee behavior. Individuals with higher levels of psychological well-being tend to demonstrate stronger motivation, higher discipline, and better adaptability when facing pressure or organizational changes. Beyond its direct influence, PWB also acts as a connecting variable between other determinants such as job satisfaction, work-life balance, and organizational support and improved performance. Overall, the review highlights that psychological well-being is not merely a personal condition but a strategic resource that significantly contributes to long term organizational productivity. Therefore, enhancing employee well-being should be integrated into human resource management practices as both a preventive measure and a long term capacity building strategy.